2002
DOI: 10.3346/jkms.2002.17.1.7
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory effects of IL-4 and IL-10 on Human Polymorphonuclear Leukocytes

Abstract: Inflammatory responses are strictly regulated by coordination of pro-inflammatory and anti-inflammatory mediators. Interleukin-4 (IL-4) and interleukin-10 (IL-10) have typically the biologic anti-inflammatory effects on monocytes, but uncertain effects on polymorphonuclear leukocytes (PMNs). The PMNs are the first line of cellular response for host defense during acute inflammation. To modify hyper-inflammatory reaction with biologic anti-inflammatory mediators, we have determined the biologic anti-inflammator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 28 publications
1
22
0
Order By: Relevance
“…50 Both increases and decreases in serum levels of IL-4 have been reported in SLE. 35,51 We did not find any significant difference in the mean levels of IL-4 between the patients and the controls.…”
Section: Discussionmentioning
confidence: 98%
“…50 Both increases and decreases in serum levels of IL-4 have been reported in SLE. 35,51 We did not find any significant difference in the mean levels of IL-4 between the patients and the controls.…”
Section: Discussionmentioning
confidence: 98%
“…Interleukin‐4 exerts anti‐inflammatory effects on human neutrophils (Lee et al., 2002) and increases neutrophil IL‐1 β production (Crepaldi et al., 2002). Effects of IL‐4 on neutrophil apoptosis have not been reported; however, both Hu et al.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that Th2 cytokines inhibit the TNF-␣/ NF-B system through activation of STAT6 acting as a transcriptional inhibitor of NF-B-dependent gene expression (14). This mechanism could also account for the inhibitory effect of IL-4 on the activation of neutrophils by LPS (15). A complete understanding of how the Th2 cytokines suppress antimicrobial activity of the airway epithelial cells remains to be determined.…”
Section: Discussionmentioning
confidence: 99%